Pelatihan Menumbuhkan Jiwa Wirausaha pada Generasi Muda Bagi Siswa Madrasah Aliyah Al-Lathifah Cikarang Barat - Kisanda Midisen; Aceng Badruzzaman; Sukron Makmun; Ali Nur Ahmad; Wulan Windiarti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service research is to train students at Al-Lathifah Senior High School West Cikarang in order to promote an entrepreneurial spirit in the next generation. The training intends to foster a creative, inventive, and solution-focused mindset in addition to giving students the information and practical skills necessary for entrepreneurship. This course makes use of case studies that are applicable to real-world situations, business simulations, talks, and debates. The study's findings show that students are becoming more knowledgeable about entrepreneurship, more interested in it, and more capable of starting and operating small enterprises. Furthermore, the pupils' attitude of independence and social responsibility was successfully formed by this instruction. As a result, it is anticipated that this training will serve as a model for other madrasas, helping to raise a new generation prepared to support the growth of the country's economy.